Respons kedelai (Glycine max) varietas Mitani terhadap pemberian beberapa jenis pupuk hayati pada tanah podsolik - Fany Panjaitan; Onesimus Ke Lele; Taufiq Bachtiar (Fakultas Pertanian Universitas Majalengka, 2023)
This study aimed to examine the growth response and yield of Mitani variety soybean plants after treating them with Rhizobium biofertilizer, Phosphate Solvent Microbes, and Azotobacter using gamma-ray irradiation technology. This research was conducted from January to May 2016 and used one-factor Randomized Block Design (RBD) with the several biofertilizer formulas treatments. The treatments level used were K0 = without fertilizer (control); K+ = 100% urea; Rhi = single strain Rhizobium; Rhi+MPF = Rhizobium Inoculant + Phosphate Solvent Microbes; and Rhi+MPF+AZ = Rhizobium + MPF + Azotobacter. Each application of biological fertilizer is mixed with 50% urea fertilizer. The data obtained were analyzed using the F-test (ANOVA) and continued with the Duncan Multiple Range Test (DMRT) at a confidence level α = 0.05. The results showed that the best plant height occurred in soybeans that were given rhizobium fertilizer and pophat solvent microorganisms. Meanwhile, the best average wet and dry weight of soybean plants (p<0.05) occurred in the 100% urea fertilizer treatment. Apart from that, the application of 100% urea fertilizer produces plants with higher water content compared to the biological fertilizer treatment. Another finding from this research is that the number of pods is not directly proportional to the weight of the root nodules. Generaly, it can be concluded that soybean plants respond more to urea fertilization than biological fertilizer.